Connective tissue graft to correct peri-implant soft tissue margin: A clinical report - Shibli, J.; D'Avila, S.; Marcantonio, E. (Mosby, Inc, 2004)
This clinical report describes the use of a subepithelial connective tissue graft to recontour a soft tissue margin discrepancy for a single-implant crown in the anterior maxilla. This procedure demonstrates that the use of soft tissue grafts to correct an esthetic deficiency may be a feasible approach to establish new and stable peri-implant soft tissue contours. The patient presented was followed for 18 months.